DEFINING ELIGIBILITY CRITERIA FOR FUNDING POLICIES AROUND IN VITRO FERTILIZATION. (30th December 2015) - Menon, Devidas; Nardelli, Alexa A.; Motan, Tarek; Klein, Kristin; Stafinski, Tania
Abstract : Objectives: This review aims to assess the state of the science around the potential impact of certain patient characteristics on the safety and effectiveness of in vitro fertilization (IVF). Methods: Following Cochrane Collaboration guidelines and the PRISMA statement, a comprehensive systematic review of reviews and recent primary studies examining the impact of paternal age and maternal age, smoking, and body mass index (BMI) on the safety and effectiveness of IVF was performed. Papers, published between January 2007 and June 2014, were independently reviewed and critically appraised by two researchers using published quality assessment tools for reviews and primary studies. Due to heterogeneity across papers (different study designs and patient selection criteria), a qualitative analysis of extracted information was performed. Results: Seventeen papers (ten systematic reviews and seven primary studies) were included. They comprised evidence from retrospective observational studies in which maternal age, BMI, and smoking status were explored as part of secondary analyses of larger studies. The majority of papers found that the likelihood of achieving a pregnancy was lower among women who were >40 years, had a BMI ≥ 25 and smoked. Advanced maternal age and BMI were also associated with higher rates of preterm birth and low birth weight. Conclusions: Based on available evidence, it may be appropriate to consider "maternal age" and "morbid obesity" in public funding policies that aim to maximize the effectiveness of IVF. However, given inconsistencies in the effect of smoking across different pregnancy-related outcomes, support for incorporating it into funding conditions appears weak.